A utilização de questões sociocientíficas na formação continuada de professores de Ciências - Costa, Luis Alexandre Lemos (2020)
Sociocientific Issues (SSI) are configured with a methodological approach to the teaching of Science from the STSE approach. Within this perspective, work with SSI can provide students with the possibility to discuss current topics based on scientific and technological knowledge and information, which generally involve ethical issues and moral values in making conscious decisions about the impacts of society and the environment. The general objective of this study was to understand the importance of SSI theory, mediated by a VLE, for the training of science teachers. And as specific objectives: a) Categorize the knowledge of teachers of Natural Sciences on the STSE approach; b) Check with science teachers which aspects related to the SSI approach are present in their pedagogical practices; c) Investigating as a Virtual Learning Environment - VLE contributes to the realization of a process of continuing education with teachers of Natural Sciences; d) Evaluate a proposal for continuing education associated with the approach of theoretical aspects in SSI following the STSE approach. Ten science teachers who work in two municipalities in the metropolitan area of Macapá (cities of Macapá and Santana) participated in this study. All teachers were inserted in the VLE (Google classroom) to carry out a theoretical training process in SSI. A questionnaire adapted for the 10 teachers was applied and semi-structured interviews (with four teachers) and final (with five teachers) were carried out. The interviews were recorded and transcribed for later analysis. The method of interpretation of meanings was used to analyze the answers to the questionnaires and transcripts of the interviews, both initial and final. The answers to the questionnaires were organized in tables and the answers to the initial and final interviews were discussed in the light of the authors related to the themes / categories that emerged through the analysis. As a result, we identified that the teachers present, in their majority, plausible views about Science, Technology and Society, and that they manifest aspects related to the SSI approach in their pedagogical practices when they highlight, that: (i) they try to contextualize and stimulate discussions in their teaching classes. sciences relating the content of the discipline to social themes; (ii) they perceive that there is an appeal to the STSE approach and SSI approach in the supporting texts proposed by the textbooks; (iii) agree that the SSI approach is a useful strategy to achieve / develop skills and competences in the area of Natural Sciences and its Technology by BNCC and; (iv) recognize that more important than teaching specific content in science classes is to work in the context in which we are inserted. And also that the use of an VLE can be considered effective in carrying out theoretical training in SSI. Considering the use of theoretical elements of SSI, as a methodological approach to the teaching of Sciences, which, being able to be mediated through a VLE, implying favorable aspects in the training of teachers, we conclude that the theoretical training in SSI, mediated through an VLE, it does contribute to the continuing education of science teachers.